Improvement of Storage Stability of Zein-Based Pickering Emulsions by the Combination of Konjac Glucomannan and L-Lysine - Song, Teng; Liu, Hui; Monto, Abdul Razak; Shi, Tong; Yuan, Li; Gao, Ruichang (Frontiers in Nutrition, 2022)
In this work, L-Lysine (Lys) was employed together with konjac glucomannan (KGM) to fabricate zein colloidal particles (ZCPs) aimed at enhancing the storage stability of Pickering emulsions. With the addition of Lys, zein-Lys colloidal particles (ZLCPs) and zein-Lys-KGM (ZLKCPs) exhibited smaller particle size (133.64 ± 1.43 nm, 162.54 ± 3.51 nm)， polydispersity index (PDI) (0.10 ± 0.029, 0.13 ± 0.022)，π value, and more adsorbed protein. Meanwhile, KGM underwent deamidation in alkaline solution, so the emulsions stabilized by ZLKCPs exhibited a solid gel-like structure with higher storage modulus (G’) and loss modulus (G’’), leading to lower fluidity and better stability. The synergistic effects of Lys and KGM improved the stability of the emulsion. Hydrophobic interactions and hydrogen bonds were the main driving forces forming colloidal particles, which was determined by driving force analysis.